The state and problems of food security ensuring in Russia. Issue 1 (January 2022) - Bukhtiyarova, Tatiana; Artamonova, Irina; Baturina, Irina
Abstract: Most researchers adhere to the opinion that food security is the ability of the state, independently from other states and international organizations, to provide its citizens with safe and quality products that are enough for an active and healthy life. At the same time, sufficient food selfprovisioning of the state increases the level of national security and ensures independence from other states. Achieving an optimal level of food security always relates to the need to level out and eliminate the consequences of various threats and risks. Threats to food security often arise simultaneously with a decline in revenue of most of the population, poorly developed social infrastructure, imbalances in the development of the agricultural and industrial sectors of the economy, etc. These positions define the research topic, the relevance of which is determined by the current implementation of food security and the identified problems of its provision.